2022
DOI: 10.3389/fvets.2022.870042
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effects of Three Polysaccharides From Abrus cantoniensis Against Cyclophosphamide-Induced Immunosuppression and Oxidative Damage

Abstract: This study was designed to systematically elucidate the immunomodulatory and antioxidant effects of three polysaccharide fractions (ACP60, ACP80, and ACPt2) from Abrus cantoniensis on cyclophosphamide (CTX)-induced immunosuppressive mice. The experimental mice were divided into 12 groups, then modeled and administrated with different doses of three polysaccharides (50, 150, 300 mg/kg/day) by gavage. The results showed that ACP could markedly recover the CTX-induced decline in immune organ and hemocytes indexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…These results implied that PHP-AuNPs were capable of maintaining the CD4 + /CD8 + lymphocytes balance (Yan & Wan, 2021). TNF-α, a critical factor for immune response, is involved in inhibiting and killing tumor cells (Qu et al, 2022). We found that PHP-AuNPs and PHP-1 can induce…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…These results implied that PHP-AuNPs were capable of maintaining the CD4 + /CD8 + lymphocytes balance (Yan & Wan, 2021). TNF-α, a critical factor for immune response, is involved in inhibiting and killing tumor cells (Qu et al, 2022). We found that PHP-AuNPs and PHP-1 can induce…”
mentioning
confidence: 70%
“…IL‐10, a type of Th2 cytokine, can suppress T‐cell activities and exhibit an immunosuppressive effect (Yan & Wan, 2021). TNF‐α, a critical factor for immune response, is involved in inhibiting and killing tumor cells (Qu et al, 2022). We found that PHP‐AuNPs and PHP‐1 can induce the expression of TNF‐α but reduce the expression of IL‐10, indicating the ability to alleviate tumor transplantation‐induced immunosuppression in H22 tumor‐bearing mice by modulating cytokine release (Figure 7d,e).…”
Section: Resultsmentioning
confidence: 99%
“…Immune activity is often considered one of the most important defenses against bacterial–viral infections, cancer invasion, or inflammation ( Zhu et al, 2016 ; Li et al, 2019 ; Qu et al, 2022 ). The central immune organs include the bursa and thymus, which have a decisive and dominant effect on peripheral lymphoid organ development ( Shirani et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, the mice's immune organs, the spleen, and the thymus were isolated and weighed. The immune organ indexes were calculated according to the following formula: The immune organ indexes (mg/g) = weight of the spleen or thymus (mg)/body weight (g) ( 30 ).…”
Section: Methodsmentioning
confidence: 99%